Geometric Influence on Microstructure and Mechanics in Welded A36 Mild Steel - Mohd Jailani, Siti Nur Fareha; Kamarudin, Kamarul azhar (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Welding is widely employed in manufacturing due to its cost-effectiveness and mechanical reliability. However, heat from welding alters the base material's microstructure, especially in the Coarse Grain Heat-Affected Zone (CGHAZ). This study investigates the effect of plate geometry on the microstructural evolution and mechanical properties of A36 mild steel welded under constant heat input. Specifically, two sets of welded plates with identical thicknesses (6 mm) but different lengths (Set A: 109mm, Set B: 198mm) were subjected to mechanical and microstructural analysis. The key tests included tensile testing, hardness testing, and optical microscopy. Results showed significant variation in cooling rates and mechanical performance due to geometric differences. Set A exhibited higher tensile strength and hardness due to faster cooling, while Set B showed improved ductility but coarser microstructures. This research emphasizes the crucial role of plate length in thermal behavior and structural performance during welding.